2011
DOI: 10.1590/s0104-11692011000500023
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality indicators in the operating room: cleaning and turnover time

Abstract: Mensuración de indicadores de calidad en un centro quirúrgico: tiempo de limpieza e intervalo entre cirugíasEste estudio exploratorio y descriptivo fue conducido en la Unidad de Centro Quirúrgico de un hospital de enseñanza teniendo por objetivos mensurar el tiempo utilizado para limpieza concurrente en sala de operación (por el Servicio de Higiene y Limpieza) y el intervalo entre las cirugías; e, investigar las asociaciones entre: tiempo de limpieza, porte de la cirugía, especialidad de la cirugía, período de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…9 Avila et al 10 observed that turnover time was dependent on duration of surgery but on the contrary review by Jericó and others published in 2011 suggested cleaning of OR duration is neither dependent on size of OR, period of the day nor on duration of surgery as previously thought. 3 Vitez and Macario 8 observed that lesser turnover time is one of the trait of good anaesthesiologist and administrators and surgeons also favour this as it improves surgical output and finishing of OR in time. This was also observed and possible in our setup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Avila et al 10 observed that turnover time was dependent on duration of surgery but on the contrary review by Jericó and others published in 2011 suggested cleaning of OR duration is neither dependent on size of OR, period of the day nor on duration of surgery as previously thought. 3 Vitez and Macario 8 observed that lesser turnover time is one of the trait of good anaesthesiologist and administrators and surgeons also favour this as it improves surgical output and finishing of OR in time. This was also observed and possible in our setup.…”
Section: Discussionmentioning
confidence: 99%
“…Turnover time (TOT) is calculated as duration of time between one patient leaving the OR and ends when the next patient enters the OR also includes time taken for setting up and cleaning of OR 1,2 .Cleaning in-between the cases is essential for reducing environmental contamination 3 . These tasks are usually completed in six to ten minutes in maximum number of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has an educational and objective character and relates to the continuous qualification of care (11) . This system considers the three dimensions proposed by Donabedian, namely structure, processes and results (12) . The structure comprises human, physical, material and financial factors; the process is related to the actions involving professionals and patients; the results correspond to the end product of the care developed (13) .…”
Section: Discussionmentioning
confidence: 99%
“…O centro cirúrgico (CC) é uma unidade complexa, com demanda de assistência espontânea e emergencial e especificidades, que necessita de controle sobre seu funcionamento a fim de prestar atendimento de qualidade. O uso de indicadores concede aos enfermeiros um norteamento para a gestão do setor, viabiliza o controle dos processos, garante a qualidade dos serviços, além de gerir sua série histórica, avaliando os processos de melhoria implantados 3, 5 .…”
Section: Introductionunclassified